Pengaruh Pemahaman, Kesadaran dan Pelayanan Perpajakan Terhadap Kepatuhan Wajib Pajak Usaha Mikro, Kecil dan Menengah (UMKM) - Iswara, Juliyawita Dwi; Mahpudin, Endang (Jurnal Ilmiah Wahana Pendidikan, 2023)
One effort to help economic development is the existence of MSMEs in Indonesia. The development and development of the country will grow even more if state financing runs smoothly. One of the government's efforts so that state financing runs smoothly is that the government requires adequate sources of state financing in the country's development which is being carried out by paying taxes. The purpose of this study was to determine the effect of understanding, awareness and tax services on MSME taxpayer compliance. This study uses the entire population of Micro, Small and Medium Enterprise taxpayers registered at the Karawang Cooperative and MSME Service in 2022, namely 95,102 MSMEs. The number of samples taken from the population in this study was using Champion MSMEs, totaling 167 MSMEs. Data was obtained by distributing questionnaires to SMEs. The sample collection technique used in this study is using Non Probability Sampling with Purposive Sampling type. In partial testing the results of the study show that awareness and tax services have an effect on taxpayer compliance, while understanding has no effect on taxpayer compliance. In simultaneous testing the results of the research show that understanding, awareness, and tax services simultaneously affect taxpayer compliance. Kata Kunci : Kesadaran, Usaha Mikro, Kecil dan Menengah (UMKM), Pelayanan dan Pemahaman Perpajakan .